Local neuronal circuitry underlying cholinergic rhythmical slow activity in CA3 area of rat hippocampal slices. - MacVicar, B A (1989)
1. Intracellular and extracellular recordings were obtained from the CA3 area of rat hippocampal slices to study cellular and synaptic mechanisms underlying rhythmic slow activity (RSA). In all impaled CA3 pyramidal neurones, continuous applications of carbachol, a non-hydrolysable cholinergic agonist, induced first a brief non-rhythmic excitation and then periodic bursts of RSA which could persist for several hours. Each burst of RSA consisted of 4-10 Hz oscillatory depolarizations which had a rise time much slower than conventional EPSPs recorded in the same cell. 2. The carbachol-induced RSA was blocked by atropine; therefore the cholinergic stimulation involved muscarinic receptors. 3. Analyses of simultaneous recordings from pairs of neurones, or a neurone and a glial cell, or a neurone and the extracellular field, indicated that carbachol-induced RSA was synchronous in a large population of CA3 pyramidal neurones. 4. Complete removal of the dentate gyrus and CA1 region did not block carbachol-induced RSA in CA3, but applications of tetrodotoxin or inorganic Ca2+ channel blockers (Cd2+, Co2+ or Mn2+) abolished carbachol-induced RSA. This suggested that the RSA involved propagation of action potentials through a local synaptic network in the CA3 area. 5. Carbachol-induced RSA was reversibly blocked by a broad-spectrum excitatory amino acid antagonist (kynurenic acid), but not by two selective N-methyl-D-aspartate (NMDA) antagonists (DL-2-amino-7-phosphonoheptanoic acid or DL-2-amino-5-phosphonovaleric acid), a GABAA antagonist (bicuculline), or a GABAB antagonist (phaclofen), suggesting that carbachol-induced RSA involved primarily non-NMDA excitatory amino acid, but not GABAergic, synapses. 6. Raising extracellular [Ca2+] beyond 7 mM, which should significantly weaken the polysynaptic recurrent excitation among CA3 pyramidal neurones, abolished carbachol-induced RSA. This suggests that the recurrent excitation among CA3 pyramidal neurones is necessary for carbachol-induced RSA in the CA3 area. However, our experiments cannot clarify whether the recurrent excitation, alone, is sufficient for carbachol-induced RSA.